1997
DOI: 10.1111/j.1469-8986.1997.tb02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of feature conjunction in transient auditor memory

Abstract: The purpose of this study was to determine whether feature conjunctions are stored in transient auditory memory. The mismatch negativity (MMN), an event-related potential that is elicited by stimuli that differ from a series of preceding stimuli, was used in this endeavour. A tone that differed from the preceding series of stimuli in the conjunction of two of its features, both present in preceding stimuli but in different combinations, was found to elicit the MMN. The data are interpreted to indicate that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 25 publications
5
60
0
Order By: Relevance
“…Nevertheless, gestalt storage is also possible in sensory memory, as revealed by the fact that an MMN is recorded after deviants differing from the standards only by the conjunction of two features (Sussman, Gomes, Nousak, Ritter, & Vaughan, 1998;Gomes, Bernstein, Ritter, Vaughan, & Miller, 1997). There were three standards intermixed in these studies, and individual features of the deviant were already present in one of the three standards, but not their conjunction.…”
Section: Mmn and Auditory Attributesmentioning
confidence: 92%
“…Nevertheless, gestalt storage is also possible in sensory memory, as revealed by the fact that an MMN is recorded after deviants differing from the standards only by the conjunction of two features (Sussman, Gomes, Nousak, Ritter, & Vaughan, 1998;Gomes, Bernstein, Ritter, Vaughan, & Miller, 1997). There were three standards intermixed in these studies, and individual features of the deviant were already present in one of the three standards, but not their conjunction.…”
Section: Mmn and Auditory Attributesmentioning
confidence: 92%
“…Michie et al (31) have suggested that the relatively greater deficit for duration MMN may derive from the fact that duration processing involves more complex neural computations than simple pitch processing. If this thesis is accurate, then one fertile area for future investigation will be in the use of so-called pattern MMNs (44)(45)(46)(47). In such studies, MMN can be obtained in healthy control subjects where to identify what is constant across stimuli requires generation of an abstract rule on a preattentive basis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a similar argument may be leveled at studies into mismatch negativity that also support the preattentive availability of auditory conjunctions (Gomes, Bernstein, Ritter, Vaughan, & Miller, 1997;Sussman, Gomes, Nousak, Ritter, & Vaughan, 1998). This is not to deny that participants are unable to automatically detect a deviant stimulus that differs from standard stimuli on the basis of a unique combination of features alone, but simply to say that this representation fails to preserve the notion of a conjunction as defined by visual stimulus processing.…”
Section: Notesmentioning
confidence: 99%